SonoPIN enables precise, noninvasive, and efficient intracellular delivery of PROTACs - Yuqi Wu; Mingyuan Liu; Ke Li; Shanglin Li; Lai Yee Phoon; John Mai; Ying Chen; Wei Yan; Shu Nakajima Lan; Joseph Rufo; Graham Milford; Ye He; et al. (Proceedings of the National Academy of Sciences, 2026)
Proteolysis-targeting chimeras (PROTACs) have emerged as a promising molecular approach for degrading undruggable proteins and for overcoming drug resistance in cancer therapy. However, their clinical translation remains limited by challenges such as poor cell membrane permeability, limited intracellular uptake, and potential off-target toxicity. To overcome these barriers, we developed Sonoporation-assisted Precise Intracellular Nanodelivery (SonoPIN), an ultrasound-driven, aptamer-guided microbubble system that enables rapid delivery of therapeutic molecules with cell selectivity. By leveraging aptamer-conjugated microbubbles and ultrasound-induced sonoporation, SonoPIN transiently permeabilizes the membranes of target cells, while leaving nontarget cells undisturbed. Using BRD4, a well-characterized oncogenic transcriptional coactivator and validated PROTAC target critically involved in cancer cell survival, as a model system, we demonstrate that SonoPIN facilitates highly efficient intracellular delivery of fluorescently labeled PROTACs. SonoPIN achieves a sevenfold increase in intracellular fluorescence after 60 s of ultrasound stimulation, resulting in a 70% reduction in BRD4 protein levels specifically in cancer cells. Importantly, BRD4 degradation is undetectable in noncancerous cells. Consequently, approximately 50% of the targeted cancer cells undergo apoptosis while nontarget cells retain more than 99% viability, underscoring the high selectivity of the SonoPIN system. Our study indicates that SonoPIN represents an innovative, noninvasive delivery platform for PROTAC therapeutics, offering a rapid and precise approach for targeted drug delivery in cancer treatment.